Analysis of Covid-19 Impact for Law and Society - Junaedi, Ulil Albab (The Indonesian Journal of International Clinical Legal Education, 2020)
Pandemic is an epidemic that has spread to several countries or even continents simultaneously affecting many people. Epidemic itself is a term used to increase the number of cases of disease suddenly in a population in a certain area. Covid-19 is a disease caused by infection with the SARS-CoV-2 virus, first identified in Wuhan City, in the Hubei province of China in December 2019. Covid-19 has spread to various countries in the world, including Indonesia. The number of positive cases of corona virus (Covid-19) in Indonesia continues to grow. Covid-19 was previously known as Novel 201 Novel Coronavirus (2019-nCoV) of respiratory disease, before the World Health Organization (WHO) declared its official name as Covid-19 in February 2020. In a pandemic, it will have an impact on human and it affects many sectors such as social and economic sectors. Of course including the legal aspects in it because this aspect was also made by humans. Health Crisis is an event or series of events that result in fatalities, injuries / illnesses, displacement, and / or the presence of potential hazards that have an impact on public health that requires quick responses beyond normal habits and inadequate health capacity. Health Crisis Response is a series of efforts that include health pre-crisis activities, Health Crisis emergency response, and post-health crisis